Recent progress towards photovoltaics' circular economy. (1st November 2022) - Rabaia, Malek Kamal Hussien; Semeraro, Concetta; Olabi, Abdul-Ghani
Abstract: Massive expansions in the global population and the global digitalization throughout the industrial revolution are causing energy security issues that are no longer environmentally affordable through conventional power generation systems. As an alternative solution, the global power capacities and production of the renewable energy systems in general and the photovoltaic technologies in particular, are significantly increasing every year. With a lifetime range of 25–40 years, the PV power plants will eventually and over their lifetime or cumulatively turn into large masses of waste. This work briefly reviews the market state of the three generations of PV and summarizes their most recent technical challenges. It is highlighted that the c-Si (Crystalline Silicon) and CdTe (Cadmium Telluride) technologies have a relatively high level of market maturity, least number of technical challenges, and most interesting space for sustainable development. Furthermore, a one-of-a-kind sustainable and circular PV industry's business model was developed, to directly and indirectly address the practical business and engineering gaps concerning environmental, economic, social, and technical factors affecting the circular transition of the PV industry. The model assisted in reviewing and discussing articles concerning material compositions, manufacturing processes, and dismantling processes. Previous reviews and surveys reported the lack of dedicated PV dismantling facilities and miscommunications between the supply chain stages and logistics. Therefore, a critical review was done on the most recent and comprehensive articles related to the optimizations and improvements of the PV industry's sustainability towards the anticipated circular economy. Additionally, this work highlights the objectives, key constraints, and major strategies of the sustainability's environmental, economic, and social pillars within the photovoltaic industry and business stages, which introduced the possible contributions of the industry 4.0 technologies. Therefore, a brief section was dedicated to the possible utilizations of Industry 4.0 throughout the critical stages of the photovoltaics' economy. Finally, a research road map was developed to assist all levels of future researches in optimizing the PV's circular economy and the overall sustainability of the industry. Graphical abstract: Image 1 Highlights: Market states, potentials, and challenges of the three generations of PV were discussed. Crystalline silicon- and CdTe- based technologies are the dominating source of PV wastes. A circular business model was developed for the PV industry. Recent improvements and optimizations towards sustainable PV lifecycle were critically discussed. A novel research roadmap is created to assist in future research on PV's circular economy.